2013
DOI: 10.1016/j.ijppaw.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Endoparasites in the feces of arctic foxes in a terrestrial ecosystem in Canada

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 43 publications
7
22
0
Order By: Relevance
“…heydorni DNA in L. gymnocercus in this study is similar to previous reports in others wild canids [29,30] and is also similar to the detected in domestic dogs. Therefore, L. gymnocercus is suggested as a natural DH of H. heydorni in Argentina and future studies should be conducted in order to confirm the presence of the closely related protozoa N. caninum.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…heydorni DNA in L. gymnocercus in this study is similar to previous reports in others wild canids [29,30] and is also similar to the detected in domestic dogs. Therefore, L. gymnocercus is suggested as a natural DH of H. heydorni in Argentina and future studies should be conducted in order to confirm the presence of the closely related protozoa N. caninum.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…Gompper et al (2003) reported a prevalence of 2% in coyote feces in New York, and Elmore et al (2013) found a single Neospora/Hammondia -like positive sample out of 95 arctic fox feces in Canada (1.1%). However, neither of these studies confirmed the identity of these oocysts using molecular methods.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively little is known about the ecology of H. heydorni in wildlife. Surveys of free-ranging wild canids that have detected H. heydorni were unable to genetically distinguish this parasite from N. caninum (Gompper et al, 2003; Elmore et al, 2013). The goal of this study was to use a series of PCR assays to determine the presence of DNA attributed to coccidia, N. caninum or H. heydorni oocysts in wild canid fecal samples (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…do not usually use canids as definitive hosts (Woodland, 1924), and the three samples containing Hymenolepis eggs found here are probably artefacts from ingested rodent prey. Hymenolepis eggs were also recorded in Arctic fox faecal samples (Elmore et al, 2013). Many helminths found in Ethiopian wolves have been recorded in domestic dogs from Debre Zeit (Yacob et al, 2007), Ambo (Zewdu et al, 2010) and Jimma (Degefu et al, 2011), all located within approximately 325 km north-west of BMNP.…”
Section: Discussionmentioning
confidence: 92%